Image Processing Based Aquaponics Monitoring System - Haryanto; Desi Anis Anggraini; Miftachul Ulum; Achmad Fiqhi Ibadillah (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2021)
Aquaponics means a culture that is very necessary to be applied, because in this system it is a combination of fish farming techniques as well as plant enlargement techniques by hydroponics. This research develops a smart aquaponics system that can control and increase the acidity level, air temperature, fish feed, and the installation of a camera to monitor fish development. In this system, there are sensors installed to retrieve data. Thus, air quality and circulation is well maintained. The results obtained from this study are to test an automatic feed system that runs well for each experiment, with an accurate proportion of 93.33%, and PH measurements that have been calibrated run well, the comparison of manual measurements using the PH meter measurement sensor gets the proportion 97, 83. for the meter Flow measurement results obtained a proportion of 91.02%, then for plant development every week got pretty good results, in the first week the plants grew 1cm after sowing, 3cm for the 2nd week, 7cm for the second week. -3. The results of measuring the weight of fish using image processing are not much different from manual measurements, the length of the fish is measured manually, it is 7 cm, and in the image it is 5.6 cm, the weight of manual fish is 11g, in the image it is 11.66g. Keywords: Aquaponics; Camera; Android; image processing, flow. Abstrak. Akuaponik merupakan suatu budaya yang sangat disarankan untuk diterapkan, karena pada sistem ini berupa kombinasi dari teknik budidaya ikan sekaligus teknik pembesaran tanaman dengan cara hidroponik. Penelitian ini merancang sistem akuaponik pintar yang bisa mengendalikan dan pantau tingkat keasaman, pakan ikan, dan pemasangan kamera untuk memantau perkembangan ikan. Dalam sistem ini, ada sensor yang dipasang untuk mengambil data,. Dengan demikian, kualitas dan sirkulasi air terjaga dengan baik. Hasil yang didapat dari penelitian ini yaitu untuk pengujian sistem pakan otomatis berjalan dengan cukup baik, dengan persentase keberhasilan 93.33 %, untuk pengukuran PH yang sudah terkalibrasi berjalan dengan baik, perbandingan pengukuran manual dengan pengukuran menggunakan sensor PH meter mendapatkan persentase keberhasilan 97.83% untuk hasil pengukuran sensor Flow meter didapatkan persentase keberhasilan sebesar 91.02%, selanjutnya untuk perkembangan tanaman setiap minggu mendapatkan hasil yang cukup baik, pada minggu pertama tanaman diperkirakan tumbuh 1cm setelah penyemaian, 3 cm untuk minggu ke-2, 7cm untuk minggu ke-3. Pengukuran berat ikan menggunakan Image processing mendapatkan hasil yang tidak jauh berbeda dengan pengukuran secara manual, panjang ikan yang diukur secara manual yaitu 7 cm, dan secara image yaitu 5.6 cm, berat ikan manual 11g, secara image 11.66g